359 Transient vs. persistent improved ejection fraction in non-ischaemic dilated cardiomyopathy. (8th December 2021) - Manca, Paolo; Stolfo, Davide; Merlo, Marco; Gregorio, Caterina; Cannatà, Antonio; Ramani, Federica; Nuzzi, Vincenzo; Lund, Lars; Savarese, Gianluigi; Sinagra, Gianfranco
Abstract: Aims: The recent definition of heart failure with improved ejection fraction (HFimpEF) outlined the importance of the longitudinal assessment of left ventricular ejection fraction (LVEF). However, long-term progression and outcomes of this subgroup are poorly explored. We sought to assess the LVEF trajectories and the correlations with outcome in non-ischaemic dilated cardiomyopathy (NICM) with improved ejection fraction (impEF). Methods and results: Consecutive NICM patients with baseline LVEF ≤40% enrolled in the Trieste Heart Muscle Disease Registry with ≥1 LVEF assessment after baseline were included. ImpEF was defined as a baseline LVEF ≤40%, a ≥ 10 point increase from baseline LVEF, and a second measurement of LVEF >40%. Transient impEF was defined by the documentation of recurrent LVEF ≤40% during follow-up. The primary endpoint was a composite of all-cause death, heart transplantation and left ventricular assist device (D/HT/LVAD). Among 800 patients, 460 (57%) had impEF (median time to improvement 13 months). Higher heart rate, smaller left atrium, absence of severe mitral regurgitation and shorter duration of disease were associated with impEF. ImpEF was independently associated with lower risk of D/HT/LVAD (HR: 0.36; 95% CI: 0.27–0.48; P < 0.001). Transient impEF was observed in 189 patients (41% of the overall impEF group) and was associated with higher risk of D/HT/LVAD compared with persistent impEF at multivariable analysis (HR: 2.54; 95% CI: 1.60–4.04). Conclusions: In NICM, we observed a 57% rate of impEF. However, recurrent decline in LVEF was observed in ≈40% of impEF patients and it was associated with an increased risk of D/HT/LVAD.